Regional specific groundwater arsenic levels and neuropsychological functioning: a cross-sectional study - Edwards, Melissa (2014)
BACKGROUND: The purpose of the study was to examine the link between GIS-estimated regional specific groundwater levels and neuropsychological functioning in a sample of individuals with and without cognitive impairment. METHODS: This cross-sectional study design analyzed data from 1390 participants (733 Alzheimer's disease, 127 Mild Cognitive Impairment, and 530 with normal cognition) enrolled in the Texas Alzheimer's Research and Care Consortium. Geographic information systems analyses were used to estimate regional specific groundwater arsenic concentrations using the Environmental Systems Research Institute and arsenic concentrations from the Texas Water Development Board. RESULTS: In the full cohort, regional specific arsenic concentrations were positively associated with language abilities (p=0.008), but associated with poorer verbal memory, immediate (p=0.008) and delayed (p<0.001) as well as poorer visual memory, immediate (p=0.02) and delayed (p<0.001). The findings varied by diagnostic category with arsenic being related with cognition most prominently among MCI cases. CONCLUSIONS: Overall, estimated regional specific groundwater arsenic levels were negatively associated with neuropsychological performance.